Shadowing and stability in p-adic dynamics - Bastos, Jefferson L. R. [UNESP]; Caprio, Danilo A. [UNESP]; Messaoudi, Ali [UNESP] (Elsevier B.V., 2021)
In this paper, we study dynamical properties as shadowing and structural stability for a class of functions on the p-adic metric spaces Z(p) and Q(p) where p >= 2 is a prime integer. (c) 2021 Elsevier Inc. All rights reserved.
Keywords: p-adic integers; Fixed point theorem; Shadowing; Structural stability